Leading sector development in Muaro Jambi District - Muhammad Safri; Slamet Rachmadi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2017)
Efforts to improve economic development and economic growth of Muaro Jambi Regency is a must. Efforts to increase economic development and economic growth can occur, if local governments are able to determine or identify priority sectors or become a base sector. Given the importance of determining and defining the right and correct strategy in the development of leading economic sectors/bases, it is necessary to conduct further study related to the development of leading sector policy in Muaro Jambi Regency. Analysis tools that are used are LQ (Location Quotient) and SWOT analysis. The results of the analysis found that of there are three sectors that are the main sector or base in Muaro Jambi Regency, namely agriculture, livestock, plantation, fishery and forestry sector, mining and quarrying sector and manufacturing industry sector. Strategies that can be done in order to maintain and develop the sector and sub-sectors/recommended base there are several alternative strategies that combine internal environmental conditions and external environment Muaro Jambi Regency is S - O (power against opportunities), S - T (power against threats) W - O (weakness to opportunity) and W - T (weakness to threat). Keywords: Location Quotient, SWOT Analysis, Base Sector